Daily life in biblical times - Borowski, Oded (Archaeology and biblical studies, 2003)
ch. 1. Introduction: the land and its people -- ch. 2. Rural life -- ch. 3. Urban life -- ch. 4. The household and life cycles -- ch. 5. Ancient Israelite arts -- ch. 6. Writing--private and official -- ch. 7. A day in the life of the Ahuzam family.